Skin photoageing: mechanisms of development and particular features of clinical manifestations - A. A. Kubanov; M. B. Zhilova; A. A. Kubanova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article discloses current concepts of mechanisms of development of skin photoageing caused by UV irradiation (UVA and UVB). Chronic exposure of skin to UV irradiation results in damage of genome DNA, development of DNA mutations, damage of proteins, membrane lipids, collagen and yellow fibers, degradation of the intercellular substance of the skin, development of a chronic inflammation, immunosuppression, melanogenesis disorders and increased angiogenesis. The authors described major clinical manifestations of skin photoageing and their histological characteristics.